Genetic diversity and evolutionary features of type VI secretion systems in Salmonella. (January 2019) - Bao, Hongxia; Zhao, Jian-Hua; Zhu, Songling; Wang, Shuang; Zhang, Jianjuan; Wang, Xiao-Yu; Hua, Bing; Liu, Chang; Liu, Huidi; Liu, Shu-Lin
Aim: Type VI secretion systems (T6SS) play key roles in bacterial pathogenesis, but their evolutionary features remain largely unclear. In this study, we conducted systematic comparisons among the documented T6SSs in Salmonella and determined their structural diversity, phylogenetic distribution and lineage-specific properties.Materials & methods: We screened 295 Salmonella genomes for 13 T6SS core components by hidden Markov models and identified 363 T6SS clusters covering types i1, i2, i3 and i4a.Results: Type i3 and i4a T6SSs were restricted to Salmonella enterica subspecies enterica and Salmonella bongori, respectively. whereas type i2 T6SSs were conserved between S. enterica subspecies, arizonae and diarizonae . S. enterica subspecies salamae, indica and houtenae harbored only type i1 T6SSs, which had wide distribution and high sequence diversity.Conclusion: The diverse Salmonella T6SSs have undergone purifying selection pressures during the bacterial evolution and may be involved in host adaptation.